2008
DOI: 10.1183/09031936.00102107
|View full text |Cite|
|
Sign up to set email alerts
|

Left ventricular diastolic dysfunction in idiopathic pulmonary fibrosis: a tissue Doppler echocardiographic study

Abstract: It was hypothesised that, apart from right ventricular (RV) dysfunction, patients with idiopathic pulmonary fibrosis (IPF) also exhibit left ventricular (LV) impairment, which may affect disease progression and prognosis. The aim of the present study was to evaluate LV performance in a cohort of IPF patients using conventional and tissue Doppler echocardiography.IPF patients exhibiting mild-to-moderate pulmonary arterial hypertension (mean age 65¡9 yrs; n522) and healthy individuals (mean age 61¡6 yrs; n522) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 28 publications
(37 reference statements)
1
32
1
1
Order By: Relevance
“…The presented spirometric and blood gas parameters were lower in our patient group in comparison to those presented by PAPADOPOULOS et al [1] (forced vital capacity (FVC): 37¡15 versus 61¡15 % predicted; arterial oxygen tension: 47¡8 versus 62¡6 mmHg (6.2¡1.0 versus 8.3¡0.8 kPa)). Also, the achieved distance in a 6-min walking test (6MWT) was shorter (255¡180 versus 450¡147 m).…”
Section: Referencescontrasting
confidence: 45%
See 4 more Smart Citations
“…The presented spirometric and blood gas parameters were lower in our patient group in comparison to those presented by PAPADOPOULOS et al [1] (forced vital capacity (FVC): 37¡15 versus 61¡15 % predicted; arterial oxygen tension: 47¡8 versus 62¡6 mmHg (6.2¡1.0 versus 8.3¡0.8 kPa)). Also, the achieved distance in a 6-min walking test (6MWT) was shorter (255¡180 versus 450¡147 m).…”
Section: Referencescontrasting
confidence: 45%
“…Most studies have demonstrated that the underfilled left ventricle found in RV pressure overload conditions, such as idiopathic pulmonary fibrosis (IPF), has relatively preserved systolic function [1,2]. GOTO et al [3] showed that increasing RV pressure by pulmonary artery constriction caused regional changes in systolic shortening in the anterior, posterior, and lateral walls of the left ventricle and the septum.…”
Section: From the Authorsmentioning
confidence: 99%
See 3 more Smart Citations